ICT solutions in intelligent organizations as challenges in a knowledge economy - Adamczewski Piotr (Management)
Solutions of the Information and Communication Technology (ICT) are the foundation of modern economic organizations in a knowledge economy. This is the case in particular in intelligent organizations, for which the advanced ICT infrastructure is the sine qua non condition for the effective knowledge management. This article is aimed at describing the role of modern ICT trends, which are described as SMAC, (Social, Mobility, Analytics, Cloud), and are becoming an essential ICT element supporting management processes. Such solutions enable to create new models of organization operations on the global markets using strategic resources, such as the knowledge supported with SMAC solutions. The arguments are illustrated with results of own research conducted by the author in 2014-2016 in selected SME’s from the Mazowieckie and Wielkopolskie rovinces and their reference to the general development trends in this area.